Ablation resistant ZrC coating modified by polymer-derived SiC/TiC nanocomposites for ultra-high temperature application. Issue 1 (January 2022) - Zhang, Yuyu; Sun, Jia; Guo, Lingxiang; Fan, Kaifei; Riedel, Ralf; Fu, Qiangang
Abstract: To improve the ablation resistance of ZrC coating on SiC-coated carbon/carbon composites above 2000 °C, SiC/TiC nanocomposites (SiC/TiC-NCs) powders derived from single-source precursor were incorporated into ZrC coating, denoted as ZrC-SiC/TiC-NCs, via supersonic atmospheric plasma spraying (SAPS). After SAPS, the incorporated SiC/TiC-NCs evolved into TiC/(SiC and Zrx Tiy C) embedded in amorphous SiC. The ablation resistance of the ZrC-SiC/TiC-NCs coating was evaluated by oxyacetylene flames with a heat flux of 4.18 MW/m 2 . For comparison, the ZrC-SiC-NCs coating without Ti modification was seriously damaged due to rapid gas denudation. The good ablation resistance of ZrC-SiC/TiC-NCs coating is mainly attributed to the distinctive "capsule-like" multi-crystalline microstructure of SiC/TiC-NCs. During ablation, TiO2 and Zrx Tiy O2, due to the oxidation of TiC and Zrx Tiy C, contributed to the formation of Zr-Ti-Si-O glass with high viscosity and low evaporation pressure, improving the ablation resistance.